Hydrological water availability, trends and allocation in the Blue Nile Basin - Awulachew, Seleshi Bekele; McCartney, Matthew P.; Shiferaw, Y. S.; Mohamed, Yasir Abbas (2008)
Rainfall varies significantly with altitude and is considerably greater in the Ethiopian highlands than on the Plains of Sudan with in the Blue Nile river. The river is the principal tributary of the main Nile River providing 62% of the flow (approximately 50 billion m3 per year) reaching Aswan. Both the temporal and spatial distribution of rainfall is governed by the movement of air masses associated with the Inter-Tropical Convergence Zone (ITCZ). The variation of flow is extreme, and any meaningful development centering water therefore requires considerable investment on water control and management to offset variability. Ethiopia currently utilizes very little of the Abay water. In contrast, Sudan uses significant volumes both for irrigation (currently in excess of 1,1 million ha) and for hydropower production. However, there remains significant potential for additional exploitation and both Ethiopia and Sudan have plans to further develop the water resources of the river. In Ethiopia, major irrigation schemes with a total area of approximately 164,000ha are planned for completion by 2010 and 815,000ha in long term. In addition, several hydropower dams, including four located on the main stem of the river, are being contemplated. In Sudan, it is planned to develop 889,000ha of additional irrigation by 2025. This paper provides an overview of the basin characteristics, hydrology of Blue Nile, brief evaluation of the current and future status of water resource development. The future development in Ethiopia for consumptive water use, limited by land potential, is an order of magnitude of 5-6km3, net water, about 10% of its runoff contribution. Similar analysis for Sudan shows possible use of 9km3. The analysis helps policy makers to base their decision on an informed basis. In Ethiopia, several major irrigation schemes, with a total area of approximately 164,000 ha, are planned for completion by 2010. In addition several hydropower dams, including four located on the main stem of the river, are being contemplated. In the Sudan, no additional hydropower is being considered, but it is planned to develop an additional 889,000 ha of irrigation by 2025. In this study the Water Evaluation and Planning (WEAP) model was used to investigate both the current situation and future water demand scenarios. Time series of flows were generated (on a monthly time-step) to determine inter-annual and seasonal variability in water availability in the major tributaries. Existing water use, related to irrigation and hydropower, was estimated from actual data. Future development scenarios were based on information obtained from commissioned projects and the national water resource master plans. This paper illustrates the value of scenarios, and the application of a relatively simple model, to assess the implications of proposed water resource development.